Is left upper lobectomy always worthwhile for early stage lung cancer? A comparison between left upper lobectomy, trisegmentectomy, and lingulectomy. Issue 4 (19th October 2017) - Aprile, Vittorio; Bertoglio, Pietro; Dini, Paolo; Palmiero, Gerardo; Mussi, Alfredo; Ambrogi, Marcello Carlo; Lucchi, Marco
Abstract : Background and Objectives: Lobectomy is the gold standard treatment for resectable Non‐Small Cell Lung Cancer (NSCLC). We compared oncological outcomes of patients undergoing a "multi‐segmentectomy" (trisegmentectomy or lingulectomy) and left upper lobectomy for early stage (T1‐2, N0) NSCLC of the left upper lobe. Methods: We retrospectively analyzed all patients with pathological early stage (T1‐T2 N0) NSCLC located in left upper lobe who underwent a lobectomy, a trisegmentectomy, or a lingulectomy between 2006 and 2013, focusing on surgical and oncological outcomes. Results: Among 159 patients, 105 patients underwent a lobectomy and 54 patients a multi‐segmentectomy (33 lingulectomy and 21 trisegmentectomy). Actuarial mean Overall Survival was 87 months (95%CI 79‐95) and 89 months (95%CI 76‐101) for lobectomies and multi‐segmentectomies, respectively ( P ‐value: 0.895), while actuarial mean Disease Free Interval was 91 months (95%CI 82‐100) and 96 months (95%CI 84‐108) respectively ( P ‐value: 0.565). We did not observe any difference in terms of local recurrence rate between the two groups ( P  = 0.337). Conclusions: Lingulectomy and trisegmentectomy lead to similar oncological outcomes compared to left upper lobectomy for T1 and T2 N0 NSCLC, and they could be used as an alternative to lobectomy even in patients with a good pulmonary function.